Responses of Aspergillus niger to selected environmental factors - Šimonovičová Alexandra (Nova Biotechnologica et Chimica, 2017)
Four wild type strains of A. niger were collected from soil and stream sediments representing environments with variable level of As, Sb, Al, Fe, Cd, Cu, and Zn contamination. Banská Štiavnica-Šobov (S), Pezinok-Kolársky vrch (P) and Slovinky (Sl) represent contaminated localities. Locality Gabčíkovo (G) was as a control site. The influence of toxic elements in these substrates on fungal growth, colony size, enzymatic activity, production of organic acids and their pelletization in water suspensions with montmorillonite was studied. The aim of our study was to find out how the wild type strains from (contaminated) environment will behave in different model solutions. We also wanted to add some new information in this area of study, because that there is some gap in the available knowledge.